RELATIONSHIP BETWEEN SLEEP QUALITY AND COGNITIVE FUNCTION IN ELDERLY IN THE TRESNA WERDHA SOCIAL ASSISTANCE KHUSNUL KHOTIMAH PEKANBARU - Wulandari, Mia; Faisal, Faisal (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Based on data on population projections in Indonesia in 2015-2045, age groups of 60 and over will continue to increase. A large number of the elderly population can be a burden if the elderly have health problems. As we get older, there will be physical appearance, function and response in daily activity. The occurrence of sleep disorders will have an impact on cognition. To determine the correlation of sleep quality with cognitive function in the elderly in UPT PSTW Khusnul Khotimah Pekanbaru. This type of research is observational analytic with the cross-sectional approach. The study was conducted at UPT PSTW Khusnul Khotimah Pekanbaru. The sampling technique used was total sampling, with 46 respondents from a total population of 58 respondents in the UPT PSTW Khusnul Khotimah Pekanbaru. Researchconducted on 46 respondents found 67% of respondents with poor sleep quality and as manyas 65% of respondents experiencing cognitive impairment. Statistical test to determine therelationship of sleep quality with cognitive function in the elderly using the SpearmanCorrelation test showed that there was a significant relationship between sleep quality andcognitive function in the elderly in UPT PSTW Khusnul Khotimah Pekanbaru with a p-valueof 0.003 (<0.05) and coefficient correlation (r) 0.427 shows the strength of the moderaterelationship with the direction of the positive correlation. Sleep quality is related to andinfluences cognitive function in the elderly at UPT PSTW Khusnul Khotimah Pekanbaru.